Fingerprint Database Variations for WiFi Positioning - Acosta, Nelson; Toloza, Juan; Kornuta, Carlos (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Indoor positioning systems calculate the position of a mobile device (MD) in an enclosed environment with relative precision. Most systems use WiFi infrastructure and several positioning techniques, where the most commonly used parameter is RSSI (Received Signal Strength Indicator). In this paper, we analyze the fingerprinting technique to calculate the error window obtained with the Euclidian distance as main metric. Build variations are presented for the Fingerprint database analyzing various statistical values to compare the precision achieved with different indicators.